Results of Surgical Treatment for Decubitus Lesions - Sakuragi, Koji; Odashiro, Koji (Orthopedics & Traumatology, 1995)
Different surgical techniques are selected for the treatment of decubitus ulcers according to size, site, age of patient and preoperative walking ability. However, there are some difficulties in selecting the best technique because of the high possibility of recurrence after surgery. We performed surgical treatment for 30 cases of decubitus ulcers, including 21 cases in the sacral region, 5 cases on the greater trochanter, and 4 cases in the ischial region. Treatment included the use of suturing, local skin flaps and musculocutaneous flaps. These results suggest that sutures and local skin flaps are indicated for cases with relatively small skin defects of less than 5×5cm. Musculocutaneous flaps provide the most stable results and are indicated for elderly patients or those with a damaged spinal cord and decubitus lesions of 5×5cm or more.